2020
DOI: 10.1021/acs.orglett.0c01244
|View full text |Cite
|
Sign up to set email alerts
|

Benzo- and Thieno-Annulated Tetracenes: A One-Pot Synthesis via Cross-Dehydrogenative Annulation

Abstract: A facile method for the direct cross-annulation of unfunctionalized tetracene is reported. The one-pot oxidative crossdehydrogenative coupling (CDC) between tetracene and aromatic compounds, such as benzene or 2-methylthiophene, furnished annulated products with an extended π-network. Moreover, relative to the benzoannulated tetracenes, thieno-annulated tetracenes exhibited notably improved photooxidative stability. This behavior stands in sharp contrast with that of tetracene and its derivatives, such as rubr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Conventionally, the π-network of acenes such as tetracene and pentacene can be extended efficiently via the 2-fold intramolecular Scholl cyclization of 5,11-diaryl tetracene or 6,13-diaryl pentacene precursors. Encouraged by our recent work on the one-pot synthesis of 1 from tetracene, we expected that similar 2-fold annulation of molecular benzene should be feasible using DDQ, which is a stronger oxidant than p -chloranil. Thus, we first examined the reaction between tetracene and benzene (2.5 equiv) mediated by a DDQ/TfOH system at ambient temperature (entry 1, Table ).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Conventionally, the π-network of acenes such as tetracene and pentacene can be extended efficiently via the 2-fold intramolecular Scholl cyclization of 5,11-diaryl tetracene or 6,13-diaryl pentacene precursors. Encouraged by our recent work on the one-pot synthesis of 1 from tetracene, we expected that similar 2-fold annulation of molecular benzene should be feasible using DDQ, which is a stronger oxidant than p -chloranil. Thus, we first examined the reaction between tetracene and benzene (2.5 equiv) mediated by a DDQ/TfOH system at ambient temperature (entry 1, Table ).…”
mentioning
confidence: 85%
“…During our studies on the synthesis of electron-deficient PAHs, which possess fully unsaturated pentagonal ring(s), we have recently demonstrated that indeno-fused tetracene 1 can be obtained directly from tetracene in a one-pot reaction via oxidative C–H/C–H cross-annulation reactions between tetracene and molecular benzene, in which two C–C bonds are formed (Figure ). Herein, we report our discovery of an unprecedented one-pot domino-type cross-coupling that creates eight C–C bonds between tetracene and six molecules of benzene to give 2 (Figure ). The results demonstrate that extended π-systems with a unique 3D structure can be obtained in one pot by an intermolecular reaction without mediation by a metal or the assistance of a specific substituent, which stands in contrast to the approach of forming multiple C–C bonds by intramolecular Scholl cyclizations with rationally designed precursors.…”
mentioning
confidence: 99%
“…Very recently, Murata reported a highly unique reaction that represents not only a rare π-extension of polyarene zigzag L -regions, but also, to our knowledge, the first cross-dehydrogenative APEX reaction between two completely unfunctionalized arenes . Under oxidative conditions, tetracene could react with benzene derivatives to yield indenotetracene products 52 (Scheme c).…”
Section: Annulative π-Extensionmentioning
confidence: 98%
“…250 Very recently, Murata reported a highly unique reaction that represents not only a rare π-extension of polyarene zigzag Lregions, but also, to our knowledge, the first cross-dehydrogenative APEX reaction between two completely unfunctionalized arenes. 251 Under oxidative conditions, tetracene could react with benzene derivatives to yield indenotetracene products 52 (Scheme 20c). These products showed significantly altered structural, electronic, and chemical properties relative to the parent tetracene, including strengthened π−π interactions in crystal packing and an improved stability towards photooxidation.…”
Section: Annulative π-Extensionmentioning
confidence: 99%
“…In 2020, Murata et al reported a cross-dehydrogenative coupling reaction between tetracene and benzene, using p -chloranil as the oxidant in the presence of triflic acid, which was found to produce indeno[1,2,3- fg ]tetracene. 497 This method also worked when benzene is replaced with t -butylbenzene, fluorobenzene, anisole and 2-methylthiophene. In the last case, compound 264.4 was formed in 29% yield ( Scheme 264 ).…”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%